Peningkatan Keterampilan Menulis Pidato Persuasif Menggunakan Model Problem Based Learning Berbantuan Multimedia bagi Siswa SMP Negeri 2 Mataram - Sahra Sahra (Universitas Pendidikan Mandalika, 2021)
This study aims to improve the skills of writing persuasive speech texts by using a multimedia-assisted Problem Based learning model for grade 9J students of SMP Negeri 2 Mataram. This research method used classroom action research. Data were obtained by using field notes, observations, tests, and documentation in the form of assignments. The data analysis technique in this research is descriptive analysis. The results of this study indicate that the application of the Problem Based Learning model assisted by multimedia can increase the activeness of students in learning to write persuasive speech texts. The increase can be seen from the percentage of activeness of 65.71% in the first cycle to 94.29% in the second cycle. In addition, the multimedia-assisted Problem Based Learning model can improve the skills of writing persuasive speech texts. This can be seen from the writing results of students who achieved the KKM in the first cycle of 74.29%, increasing to 100%.